PEMBERDAYAAN EKONOMI IBU PKK MELALUI GALERI BANK SAMPAH DAN URBAN FARMING MENUJU PEMBANGUNAN LINGKUNGAN BERKELANJUTAN DI KAMPUNG MERGOSONO - Fawwaz, Muhammad Iqbal; Akbar, Muhammad Fikri; Churiyah, Madziatul; Sholikhan (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Waste management is a pressing concern in urban areas, and one effective solution is the establishment of a waste bank. In Kampung Mergosono, addressing waste issues involves active participation from the PKK (Family Welfare Movement) mothers. The goal is to educate and empower the community in waste management, fostering social awareness and behavior change through the "Waste Bank Gallery" for sustainable environmental development. The target audience is the PKK mothers, who are expected to lead the implementation of the waste bank gallery. The approach includes counseling on waste issues, waste management solutions, the Waste Bank Gallery program, waste handling procedures, task delegation, schedules, involved parties, and the benefits of proper waste management. Additionally, practical recycling of valuable waste materials and the use of organic waste as fertilizer for urban farming are taught. The outcome shows effective dissemination of the Waste Bank Gallery program, contributing to improved waste management in the area.